From Internet to the streets: An approach to activism in Aguascalientes, Mexico - Flores Márquez, Dorismilda (AoIR Selected Papers of Internet Research, 2013)
In this paper, I present the outcomes of an empirical exploration on activism and online communication practices in a Mexican city, on the case of #YoSoy132 Aguascalientes. It is part of a doctoral research in progress, that lies on the theoretical approach of the three degrees of communication and on the methodological perspective of multi-sited ethnography. This experience leads to regard the links between online communication, physical action and media coverage, in activism, and the challenging implications for their study.